"We're just existing, not living!" Mortgage stress and the concealed costs of coping with crisis. Issue 5 (4th July 2017) - Waldron, Richard; Redmond, Declan
Abstract: Following the financial crisis, an extensive literature has examined the vulnerabilities facing mortgagors in default and foreclosure. However, in addition to these "overt casualties" of the crash, many households are struggling to meet their mortgage payments by enduring severe cutbacks to their quality of life. The experiences of these "unrevealed casualties" of the financial crisis and the coping strategies they employ to respond to mortgage stress remain under-explored. Drawing on survey data of Irish mortgagors ( n = 433), this paper examines the impacts of mortgage stress upon quality of life and mortgagors' coping strategies to respond to their financial difficulties. The findings suggest that mortgage stress affects a broader range of households than previously considered; mortgage stressed households adopt a range of expenditure, employment, finance and housing-related responses; and more punitive responses correlate with greater mortgage stress levels, thereby providing a fuller account of the real cost of coping with the crisis impacts.